Development and Transportation Pathway Evaluation of Liposomes with Bile Acids for Enhancing the Blood-Brain Barrier Penetration of Methotrexate - Natthan Charernsriwilaiwat; Rattanan Thaitrong; Samarwadee Plianwong; Praneet Opanasopit; Pucharee Songprakhon; Thirapit Subongkot (Pharmaceutics)
Background/Objectives: The purpose of this study was to create bile acid-containing liposomes to improve methotrexate blood-brain barrier penetration and to assess the liposome transportation mechanism across the blood–brain barrier. Methods: The improvement of liposome penetration was investigated utilizing human brain microvascular endothelial cells in an in vitro blood-brain barrier model. Using confocal laser scanning microscopy (CLSM) and flow cytometry, liposomes were labeled with fluorescent phospholipids to facilitate their passage across the blood–brain barrier. Results: The produced liposomes with bile acid exhibited a negative surface charge and an average particle size of between 30 and 148 nm. According to an in vitro blood-brain barrier penetration study, the methotrexate penetration was increased by liposomes containing 1% glycocholic acid but not by liposomes containing taurocholic acid. For transport pathway evaluation across the blood-brain barrier of these liposomes, CLSM revealed that fluorescent liposomes were present inside cells treated with specific endocytosis inhibitors, indicating that the cellular internalization of the particles was not involved in endocytosis. Conclusions: Liposomes supplemented with 1% glycocholic acid could enhance the penetration of methotrexate across the blood-brain barrier, while taurocholic acid could not. The transport of liposomes with 1% glycocholic acid across the blood-brain barrier occurs via the transcellular pathway through which it penetrates cells. In contrast, the paracellular pathway was a minor pathway.